Induktivisme-Empirisisme Francis Bacon dan Relevansinya Bagi Ilmu-Ilmu Keagamaan - Setianingsih, Yeni (Indonesian Journal of Islamic Theology and Philosophy, 2019)
Based on observations made by the senses on events that occur around humans, in the treasury of philosophy there are two ways to draw a conclusion, namely deductive and inductive. Francis Bacon is a philosopher who is known by the principle of thinking that is Induktivism-Empiricism. This method can also be applied in the study of religious knowledge that is related to the establishment of law or known as figh. This article will explore how Bacon's Inductivism-Empiricalism thought and its relevance to the science of religion. This article uses a descriptive analysis method. Bacon's thinking is that conclusions are drawn from something specific and then drawn to the general. With an objective assessment, this method is able to solve religious problems that are now popping up a lot.